Run & jump [videorecording (DVD)] - Green, Steph; Peake, Maxine; Forte, Will; MacLiam, Edward, 1976- (IFC Films, 2014)
After her husband suffers a debilitating stroke, a spirited Irish housewife struggles to keep her family together in the wake of tragedy. Help comes in the form of American doctor, whose research grant for documenting the family's recovery process takes care of finances but also requires that the straight-laced doctor live with the chaotic Casey family for two months.